2009 Second International Conference on Emerging Trends in Engineering &Amp; Technology 2009
DOI: 10.1109/icetet.2009.121
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wireless IEEE802.11n Encryption Methods on Network Performance of Operating Systems

Abstract: Wireless technologies continue to play an increasing role in all kinds of networks. Wireless options are increasing and the cost of these technologies continues to decrease. It is anticipated that wireless networking of all types will become more prevalent in the years to come. However security and performance is a major concern. In this research, performance of wireless IEEE802.11n is evaluated on four operating systems, namely Windows XP, Vista, Server 2008 and Ubuntu. A network is created on a test-bed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The test bed is under a two-nod 802.11n draft wireless network environment. The result of this research still shows that the most recent encryption protocol is comparatively the best one [19]. According to these researches, the outcome data of test bed based experiment is quite unstable as the real test bed environment may have various unpredictable elements.…”
Section: Wlan Performance Evaluationmentioning
confidence: 93%
“…The test bed is under a two-nod 802.11n draft wireless network environment. The result of this research still shows that the most recent encryption protocol is comparatively the best one [19]. According to these researches, the outcome data of test bed based experiment is quite unstable as the real test bed environment may have various unpredictable elements.…”
Section: Wlan Performance Evaluationmentioning
confidence: 93%
“…In [5], presented are results of performance comparison of IEEE 802.11n encryption methods on four operating systems, for both TCP and UDP tra c. is research has shown that operating systems perform di erently within IEEE 802.11n wireless network and its encryption algorithms. It is also shown that WPA2 behaves signicantly di erently to the other encryption methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An anomaly is detected when some mobile hosts use a lower bitrate than others, degrading the performance of all hosts. The anomaly is analyzed theoretically, by means of simulations, and in testbeds with several performance measurements conducted with netperf 8 , tcpperf 9 , and udpperf 10 . A comparative study of the impact of wireless encryption methods over different operating systems is presented in [8].…”
mentioning
confidence: 99%
“…The anomaly is analyzed theoretically, by means of simulations, and in testbeds with several performance measurements conducted with netperf 8 , tcpperf 9 , and udpperf 10 . A comparative study of the impact of wireless encryption methods over different operating systems is presented in [8]. The authors evaluate Windows XP, Windows Vista, Windows Server 2008, and Ubuntu, carrying out several experiments to evaluate the performance of TCP and UDP, using WEP-64, WEP-128, WPA, and WPA2.…”
mentioning
confidence: 99%